The state of collaboration: an analysis of form and function in Colorado's natural resource collaboratives - Huayhuaca, Ch'aska, author; Reid, Robin S., advisor; Fernández-Giménez, María, advisor; Schultz, Courtney, committee member; Theobald, David, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: collaborative environmental governance; Colorado; natural resource collaboration; collaborative organizations; collaborative conservation; initial conditions